Sovereignty and Power Differentials. Paradigms for a Rereading of the Este Reform of Feudal Justice (1763): Peer-reviewed article (Italian Review of Legal History, 2022)
This work investigates the innovation introduced by the Este Act of 12 September 1763 reforming, at paragraph XIII, the criminal justice administered at feudal lords’ level. The specific problem that this new legislation raised and still raises lies in the marked ambivalence of its overall significance. The motivations behind the reform, at least the official ones, were actually clear, given the problems of feudal justice that the sources envisaged. Nevertheless, while on the one side the Act brought the feudal courts strictly under the control of the highest ducal court, it did not seem, on the other side, to aim at erasing the framework of the plural entitlement of power. In this sense, even the power to pardon seemed to remain intact in the hands of the feudal lords. Moreover, such ambiguity of significance intensifies when we consider the feudal grievances raised against the reform. The one and the others tended, in fact, to highlight certain aspects and adumbrate others in the meantime: one pressed to reinforce the unitary mark of justice, the others to assert such a separate administration of it that would have never allowed outside interference. Sovereign and feudal powers thus ended up confronting each other in a heated dispute, at the end of which the danger to the autonomy of feudal jurisdictions seemed to recede. But this by no means seems to solve the underlying issue: earlier precedents had in fact already limited, and even incisively, the exercise of feudal powers. The actual scope of the novelty introduced by the 1763 reform is, therefore, unclear. In order to reconstruct the significance of the dispute as well as of the reform, the functioning of feudal powers and their intersections with the Este sovereignty in their Dukedom have to be scrutinised. This means considering the new legislation in the light of its proper overall context and juridical order. Accordingly, the paper seeks to investigate the specific nature of that order, in particular what was the prevailing character (if there was any) between the plural entitlement or even «ownership» of public power and the shared exercise of that same power. In so doing the interpretation of the reform of 1763 will neither simplistically adhere to the feudal rhetoric hoping for the widest possible separation of its power from the ducal sovereignty, nor follow the idea of an overcome of legal pluralism driven by the central power. By contrast, the paper will argue that such plural order was tenaciously vital in many ways. The enormous variability of the feudal lords’ prerogatives reflected a juridicity often constituted by an extremely heterogeneous and punctiform ius singulare, differing in part even from investiture to investiture. The question will nevertheless be examined whether a more secure perimeter could not be traced, which could serve as a framework for the contingent and ever-changing social balances and power relations between sovereign and feudal aristocracy. Lastly, it will also be verified whether the allocation of power over the territory took the only form of the feudal juridical relationship. In particular, it will be explored whether in every field of power the autonomy of feudal orders and the paradigms of sovereignty always operated in the same way, or whether this entitlement of powers sometimes was differently shaped.
Keywords: Feudalism; iurisdictio; composite State; centralization; sovereignty